Patrinia herba aqueous extract on the proliferation, apoptosis, invasion and migration of hepatocellular carcinoma cells - Guan, Zhenhua; Chen, Jing; Li, Xueliang (Cellular and Molecular Biology, 2020)
This study aims to study the effect and mechanism of Patrinia herba aqueous extract on proliferation, apoptosis, invasion and migration of hepatocellular carcinoma cells. Hepatocellular carcinoma cells MHCC97-H were treated with 2.5, 5, 10 mg/mL P. herba aqueous extract, cell counting kit 8 (CCK-8), flow cytometry, plate cloning experiments, and Transwell measured cell survival, apoptosis, colony formation, invasion, and migration, respectively. Real-time quantitative PCR (qPCR) and western blot were used to detect long non-coding RNA (lncRNA) HTR2A-AS1 and expression of proteins P21, Caspase-3, E-cadherin and matrix metalloproteinase-2 (MMP-2), respectively. Transfected pcDNA3.1-HTR2A-AS1 in MHCC97-H cells, or transfected si-HTR2A-AS1 and treat with 10 mg/mL P. herba aqueous extract to evaluate their roles in cell proliferation, apoptosis, invasion, and migration. Different concentrations of P. herba aqueous extract significantly reduced the survival rate, colony formation, number of migrating cells, number of invading cells, and MMP-2 protein expression of MHCC97-H cells, and obviously increased the cell apoptosis rate, the expression levels of Caspase-3, E-cadherin protein and HTR2A-AS1 (P<0.05), which were all concentration-dependent. Overexpression of HTR2A-AS1 evidently decreased the survival rate, colony formation, number of migrating cells, number of invading cells, and MMP-2 protein levels in MHCC97-H cells, while remarkably enhanced the apoptosis rate of cells, P21, Caspase-3, and E-cadherin protein levels and HTR2A-AS1 expression level (P<0.05). Inhibition of HTR2A-AS1 greatly improved the survival rate, the number of clone formation, the number of migrating cells, the number of invading cells and the expression of MMP-2 protein of MHCC97-H cells treated with P. herba aqueous extract, dramatically reducing the cell apoptosis rate, P21, Caspase-3, E-cadherin protein levels and HTR2A-AS1 expression levels (P<0.05). P. herba aqueous extract may inhibit the proliferation, invasion and migration of hepatocellular carcinoma cells by up-regulating the expression of HTR2A-AS1 in hepatocellular carcinoma cells and induce apoptosis.